f ( x ) = a x a x a x + a x f(x)=\frac{a^x-a^{-x}}{a^x+a^{-x}}

Algebra Level 2

For f ( x ) = a x a x a x + a x ( a 1 , a > 0 ) , f(x)=\frac{a^x-a^{-x}}{a^x+a^{-x}} ( a \neq 1, a>0), if f ( k ) = 10 , f(k)=10, what is the value of f ( 2 k ) ? f(2k)?

19 101 \frac{19}{101} 20 101 \frac{20}{101} 22 101 \frac{22}{101} 21 101 \frac{21}{101}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sidharth Kapur
Mar 10, 2014

We start by rearranging f ( x ) f (x) .

f ( x ) = a x a x a x + a x = a x 1 a x a x + 1 a x = a 2 x 1 a 2 x + 1 = 1 2 a 2 x + 1 f (x) = \dfrac{a^x - a^{-x}} {a^x + a^{-x}} = \dfrac{a^x - \frac{1}{a^x} }{a^x + \frac{1}{a^x}} = \dfrac{a^{2 x} - 1} {a^{2 x} + 1} = 1 - \dfrac{2}{a^{2 x} + 1}

Therefore

f ( k ) = 1 2 a 2 k + 1 = 10 f ( k) = 1 - \dfrac{2}{a^{2 k} + 1} = 10

9 = 2 a 2 k + 1 - 9 = \dfrac{2}{a^{2 k} + 1}

a 2 k + 1 = 2 9 a^{2 k} + 1 = - \frac{2}{9}

a 2 k = 11 9 a^{2 k} = - \frac{11}{9}

We would like to find a 4 k a^{4 k} .

a 4 k = 121 81 a^{4 k} = \frac{121}{81}

f ( 2 k ) = 1 2 a 4 k + 1 = 1 2 121 81 + 1 f ( 2 k) = 1 - \dfrac{2}{a^{4 k} + 1} = 1 - \dfrac{2}{\frac{121}{81} + 1}

This simplifies to 20 101 \frac{20}{101} .

The third statement says 'We would like to find a^2k' I thought it could b more good if it was a^4k and so on for aftermath....

Vishal Ajwani - 7 years, 2 months ago

Log in to reply

Thanks for the correction! I have fixed it now.

Sidharth Kapur - 7 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...